Geology, U-Pb dating and 3D visualisation of late-orogenic Klenov Pluton (Pelhřimov Core Complex, Central European Variscides) - Jaroslava Pertoldová; Kryštof Verner; David Buriánek; Jan Valenta; Barbora Dudíková; Zuzana Skácelová; Jan Jelének; Jan Jelínek; Kenneth Johnson; Otmar Petyniak; Petra Hejtmánková (Journal of Maps)
The geological map of the Klenov Pluton (Moldanubian Batholith), and its 3D visualization, brings the new findings in the context of granite emplacement within late-Variscan settings. The Klenov Pluton has a peraluminous composition resulting from partial melting of metasedimentary sources and subsequent differentiation. The new ages 327.14 ± 0.21 Ma and 327.80 ± 0.37 Ma, reflect the narrow time-span of magma emplacement and cooling. The 327 Ma Klenov Pluton was emplaced syntectonically as a ‘sheet-like’ granite intrusion at depth ca. 10 kilometers during the later stages of the Pelhřimov Core Complex exhumation (at ca. 329 to 327 Ma) associated with ∼N–S oriented compression. Gravity modelling suggests that the Klenov Pluton has an asymmetric shape where its western flank is parallel to the ∼NW moderately dipping Pelhřimov Core Complex. The eastern margin of the Pluton is shallower and has been later modified by ∼SE-side-up normal faulting (Lodhéřov Fault Zone).